Comparison and harmonization of public revenue systems, especially of fiscal systems (York, England : International Institute of Public Finance, 1966)
This volume contains the reports of the 19th session of the institute , held at Luxembourg in September 1963. It also contains the addresses given at the opening session of the congress, the general report, the special reports, a summary of the report of the Secretary General and of the proceedings of the General Assembly as well as the list of the members of the Committee of Direction.
Includes bibliographical footnotes.
hza 31/01/2019
Loans
Keywords: Taxation; International economic integration--Congresses.; International economic integration